Widespread Occurrence of Coral Growth Anomalies in the Republic of Maldives - Chiara Bises; Inga Dehnert; Greta Aeby; Michelle Dennis; Jacopo Gobbato; Jessica Hodge; Miriam Staiger; Federica Siena; Paolo Galli; Simone Montano (Diversity, 2023)
In the last decades, there has been a concerning increase in the frequency and severity of coral disease outbreaks on a global scale, resulting in significant damage to the coral reef ecosystem and biodiversity. Growth anomalies (GAs) have been increasingly observed, with significantly higher occurrences in larger and older coral colonies compared to their smaller counterparts. However, there is a notable lack of knowledge and reports regarding growth anomalies in the Maldivian region. Here, we provide the first evidence of four distinct growth anomalies on three coral species, respectively on Acropora sp., Montipora sp., and Pachyseris speciosa, observed across four different locations across three atolls within the Maldivian Archipelago.